Omnipresent Invisibility. The Identity of the Translator: the Case of Paweł Hulka-Laskowski and His Translation of the Self and Sex Book Series - Sobesto, Joanna (Porównania, 2020)
The main aim of this paper is to look at the biography of Paweł Hulka-Laskowski, a theologian, pedagogue, writer and diplomat, through the perspective of his perennial work as a translator. Unlike his contemporaries – translators active in the interwar period in Poland, Hulka-Laskowski is still well-recognized, the collective memory of him is, however, refracted, often omits his translation work. The paper demonstrates that his experience as a translator was key to his entire professional and private life – both were related to the translation of the series for American teenagers What a Young Man (Woman) Ought to Know.